2008
DOI: 10.1186/1471-2164-9-449
|View full text |Cite
|
Sign up to set email alerts
|

The missing link: Bordetella petrii is endowed with both the metabolic versatility of environmental bacteria and virulence traits of pathogenic Bordetellae

Abstract: Background: Bordetella petrii is the only environmental species hitherto found among the otherwise host-restricted and pathogenic members of the genus Bordetella. Phylogenetically, it connects the pathogenic Bordetellae and environmental bacteria of the genera Achromobacter and Alcaligenes, which are opportunistic pathogens. B. petrii strains have been isolated from very different environmental niches, including river sediment, polluted soil, marine sponges and a grass root. Recently, clinical isolates associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 53 publications
2
104
0
1
Order By: Relevance
“…strain P51 (van der Meer et al, 1991) and in Ralstonia sp. strain PS12 (Beil et al, 1999;Müller et al, 2003) are carried on transposons, or are localized on genomic islands, as in Bordetella petrii (Gross et al, 2008). Whether the upper pathway genes of strain GJ31 belong to its core genome or have been recruited by horizontal gene transfer remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…strain P51 (van der Meer et al, 1991) and in Ralstonia sp. strain PS12 (Beil et al, 1999;Müller et al, 2003) are carried on transposons, or are localized on genomic islands, as in Bordetella petrii (Gross et al, 2008). Whether the upper pathway genes of strain GJ31 belong to its core genome or have been recruited by horizontal gene transfer remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Only four species, B. petrii (von Wintzingerode et al, 2001) and the three novel species mentioned above, were isolated from the environment. However, whole genome analysis verified that B. petrii has pathogenic genes in its genome (Gross et al, 2008). Interestingly, B. petrii has been isolated from clinical samples since the initial finding by von Wintzingerode et al (2001) (e.g., Fry et al, 2005;Le Coustumier et al, 2011;Stark et al, 2007).…”
Section: -7 Bordetellamentioning
confidence: 99%
“…In general, pathogenic Bordetella species are able to grow at temperatures around 37∞C and are fastidious, which is likely due to host-parasite interactions. Based on the whole genome sequence of B. petrii, Gross et al (2008) suggested that this bacterium might grow in a variety of environments because it has remarkable metabolic versatility. Most pathogenic species of the genus Bordetella lack metabolic versatility, so they are host-restricted pathogens.…”
Section: -7 Bordetellamentioning
confidence: 99%
“…Gly-CCC and PaVRFPA04GI Gly-CCC that contains many multiantibiotics resistance genes has been named as GI6 [9] . The two GIs, namely PAO1GI-1 and PA14GI-6, associated with tRNA Gly-CCC gene have been determined in P. aeruginosa PAO1 and UCBPP-PA14 [10] .…”
Section: A Two Genomic Islands Were Integrated Into 5' and 3'mentioning
confidence: 99%